The direct impact of team leadership on implicit coordination of a team and the role of trust as a mediator - Quintal, Pedro Nunes (2016)
The purpose of this master thesis is the study of the relationship between leadership of a team and the achievement of implicit coordination, both directly and indirectly, through trust within the team. Data was collected by distributing a survey and by doing a laboratory study. From all the research made, it was expected that leadership would boost trust and implicit coordination, and that trust would also boost implicit coordination. The results confirmed that and showed that the different types of leadership functions have a positive effect on the level of implicit coordination a team can achieve, through the development of trust within a team.